2015 IEEE International Reliability Physics Symposium 2015
DOI: 10.1109/irps.2015.7112744
|View full text |Cite
|
Sign up to set email alerts
|

Understanding pulsed-cycling variability and endurance in HfO<inf>x</inf> RRAM

Abstract: Resistive switching memory (RRAM) devices based on metal oxides are receiving strong interest for future highdensity stand-alone memories and storage class memories. To explore possible applications of RRAM, the set/reset variability and cycling endurance must be addressed and understood. This work shows a comprehensive study of pulsed-operated variability and endurance in HfO x-RRAM. We analysed the dependence of switching variability on operation current, voltage and pulsewidth, providing guidelines to optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 15 publications
0
8
1
Order By: Relevance
“…Compared to recently reported distributions [6,8], the window between HRS and LRS is well defined and the cellto-cell as well as the cycle-to-cycle variability is strongly reduced.…”
Section: Resultscontrasting
confidence: 64%
“…Compared to recently reported distributions [6,8], the window between HRS and LRS is well defined and the cellto-cell as well as the cycle-to-cycle variability is strongly reduced.…”
Section: Resultscontrasting
confidence: 64%
“…Afterwards, 1k reset/set cycles were performed on every batch of 128 RRAM devices in order to test the switching endurance for every pulse width considered. As shown in Figure 3, it can be concluded that the voltage amplitude required to switch the RRAM devices increases when the programming pulse width is reduced [21,22]. This increase is even more noticeable when pulse widths of 100 and 50 ns are used.…”
Section: Resultsmentioning
confidence: 88%
“…Such a good performance achieved regardless the pulse width employed could be explained as follows. According to Balatti et al [21], there is an optimal combination of the programming pulse width and the voltage amplitude in order to achieve the best switching endurance. The step-by-step approach implemented in the core of the ISPVA leads to a dynamic tailoring of this combination of the two programming parameters (see Figure 3) every cycle.…”
Section: Resultsmentioning
confidence: 99%
“…However, there are still many obstacles to be overcome to easily implement RRAM memory arrays in current state-of-the-art CMOS circuits [ 5 , 6 ]. One of the key challenges in sizable RRAM array is found in the variation existing between and within cells [ 7 10 ]. Many models and simulations have been proposed to describe the stochastic generation/recombination process of oxygen vacancy (Vo-) in transition metal oxide (TMO) film [ 11 14 ].…”
Section: Introductionmentioning
confidence: 99%